(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
From January through March, 2020, the co-authors worked together at the Samarqand Institute for Teacher Recertification, providing a cohort of teachers with intensive training to become STEM coaches. Allan was a DAST Fulbright Fellow providing STEM expertise from the US and Dilbar is the Assistant Director at the Institute who organized the project. Allan worked with a cohort of 25 teachers for 5 weeks introducing them to STEM principles from the US systems and training them to become STEM coaches for area teachers. Allan was also able to visit multiple general schools in the Samarqand region, as well as the Presidential School in Khiva for teacher presentations and model lessons. This paper is a summary of the project, presented in the hopes that it can provide inspiration for similar work throughout Uzbekistan.